2015
DOI: 10.1098/rspb.2015.0583
|View full text |Cite
|
Sign up to set email alerts
|

Extrapolating from local ecological processes to genus-wide patterns in colour polymorphism in South AfricanProtea

Abstract: Polymorphic traits are central to many fundamental discoveries in evolution, yet why they are found in some species and not others remains poorly understood. We use the African genus Protea-within which more than 40% of species have co-occurring pink and white floral colour morphs-to ask whether convergent evolution and ecological similarity could explain the genus-wide pattern of polymorphism. First, we identified environmental correlates of pink morph frequency across 28 populations of four species. Second, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…). Thus, Carlson & Holsinger () found that flower colour polymorphic species of Protea inhabiting the Cape region showed broader elevational gradients than monomorphic species. We postulate that the evolutionary processes maintaining polymorphism in spatially and temporally variable environments, such as the Mediterranean Basin (Thompson ), will result in a continuum of geographic patterns of FCP (morph compositions and relative frequencies).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…). Thus, Carlson & Holsinger () found that flower colour polymorphic species of Protea inhabiting the Cape region showed broader elevational gradients than monomorphic species. We postulate that the evolutionary processes maintaining polymorphism in spatially and temporally variable environments, such as the Mediterranean Basin (Thompson ), will result in a continuum of geographic patterns of FCP (morph compositions and relative frequencies).…”
Section: Discussionmentioning
confidence: 99%
“…; Dick et al . ; Carlson & Holsinger ), resulting in a geographic pattern of morph distribution that contributes to divergence.…”
Section: The Role Of Fcp In Driving Speciationmentioning
confidence: 99%
See 2 more Smart Citations
“…Divergence between species is enabled by phenotypic variation present in natural populations (Gompel et al, 2005;Wittkopp et al, 2009;Sanger et al, 2013;Carlson et al, 2015) and biased along both genetic and developmental lines of least resistance (Schluter, 1996), such as those arising through sex-specific development or developmental processes biased towards particular reproductive or trophic morphs (Lorch et al, 2003;West-Eberhard, 2003;Smith et al, 2008;Aubin-Horth & Renn, 2009). For example, many invertebrate and vertebrate species have diverged most obviously in the expression of secondary sexual traits, which also account for the greatest phenotypic variation within populations (Emlen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%